Modified battery zinc powder and method for preparing the same

CN123017942APending Publication Date: 2026-10-30SHENZHEN NONFEMET TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611324672.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本申请提供了一种改性电池锌粉及其制备方法,旨在改善现有锌粉存在大量高活性位点、容易发生腐蚀和析氢等副反应,造成电池容量衰减快的问题

Benefits of technology

(1)本申请通过在锌粉基体表面原位生成呈点状均匀分布的氧化锌颗粒,并且确保锌粉基体表面裸露金属锌区域的面积占比为15%~60%,可提升改性电池锌粉的比表面积,并钝化锌粉基体表面的高活性缺陷位点,同时,锌粉基体表面裸露金属锌区域的面积至少保留15%,可满足锌粉基本的导电性和电化学活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017942A_ABST
    Figure CN123017942A_ABST
Patent Text Reader

Abstract

The application discloses modified battery zinc powder and a preparation method thereof, and relates to the field of battery negative materials. The modified battery zinc powder comprises a zinc powder base body and a discontinuous oxidation layer in-situ grown on the surface of the zinc powder base body, and the discontinuous oxidation layer is in the form of point-like uniformly distributed zinc oxide particles, wherein the area ratio of the exposed metal zinc region on the surface of the zinc powder base body is 15-60%, and the particle size range of the zinc oxide particles is 50-800 nm. The application can improve the specific surface area of the modified battery zinc powder by in-situ generating point-like uniformly distributed zinc oxide particles on the surface of the zinc powder base body and ensuring that the surface of the modified battery zinc powder has an exposed metal zinc region with a suitable area, and can passivate the high-activity defect sites on the surface of the zinc powder base body under the condition of meeting the basic conductivity and electrochemical activity of the zinc powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery anode materials, and in particular to a modified battery zinc powder and its preparation method. Background Technology

[0002] Zinc-based batteries offer advantages such as low cost, environmental friendliness, high safety, and excellent electrochemical performance, making them widely used in energy storage and consumer power applications, including alkaline zinc-manganese batteries and aqueous zinc-ion batteries. Zinc powder is the core active material of the negative electrode in zinc-based batteries; its surface structure, conductivity, and interfacial stability directly determine the battery's discharge capacity, self-discharge performance, and cycle life. Therefore, zinc powder modification is a key technological direction for improving the overall performance of zinc-based batteries.

[0003] Existing commercially available virgin zinc powder has a large number of highly active sites, such as lattice defects, on its surface, resulting in poor surface uniformity. During battery operation, these highly active sites on the zinc powder surface are prone to side reactions such as corrosion and hydrogen evolution with the electrolyte, leading to severe self-discharge, rapid capacity decay, and also easily inducing zinc dendrite growth, damaging the electrode interface and shortening battery life. Summary of the Invention

[0004] This application provides a modified battery zinc powder and its preparation method, aiming to improve the problem that existing zinc powder has a large number of highly active sites, is prone to corrosion and hydrogen evolution side reactions, and causes rapid battery capacity decay.

[0005] Firstly, this application provides a modified battery zinc powder as follows: A modified battery zinc powder, comprising a zinc powder matrix and a discontinuous oxide layer grown in situ on the surface of the zinc powder matrix, wherein the discontinuous oxide layer consists of zinc oxide particles uniformly distributed in a dotted pattern, wherein the area of ​​the exposed metallic zinc region on the surface of the zinc powder matrix accounts for 15% to 60%, and the particle size of the zinc oxide particles ranges from 50 nm to 800 nm.

[0006] This application improves the specific surface area of ​​modified battery zinc powder by generating uniformly distributed zinc oxide particles in situ on the surface of zinc powder matrix and ensuring that the area of ​​exposed metallic zinc on the surface of zinc powder matrix accounts for 15% to 60%. It also passivates highly active defect sites on the surface of zinc powder matrix and weakens the self-discharge phenomenon of battery. At the same time, the area of ​​exposed metallic zinc on the surface of zinc powder matrix is ​​at least 15%, which can meet the basic conductivity and electrochemical activity of zinc powder.

[0007] Preferably, the area of ​​the exposed metallic zinc region on the surface of the zinc powder matrix accounts for 20% to 40%.

[0008] Preferably, the zinc oxide particles have a particle size range of 100 nm to 500 nm. More preferably, the zinc oxide particles have a particle size range of 200 nm to 400 nm.

[0009] Secondly, the first method for preparing modified battery zinc powder provided in this application is as follows: A method for preparing modified battery zinc powder, used in any one of the modified battery zinc powders described above, comprising the following steps: S11. Take battery-grade zinc powder raw material, and remove coarse particles and ultrafine floating powder by sieving and air classification to obtain a pure and uniform zinc powder matrix. S12. The zinc powder matrix obtained in step S11 is fed into the heat treatment chamber at a feeding rate of 0.5 kg / min to 10 kg / min. Simultaneously, a mixed hot gas flow with an oxygen volume fraction of 1% to 15% and a temperature of 100℃ to 400℃ is injected into the heat treatment chamber to perform hot gas modification on the zinc powder matrix, so as to grow a discontinuous oxide layer in situ on the zinc powder surface; the volume-to-mass ratio of the mixed hot gas flow to the zinc powder matrix is ​​0.01 m³ / min. 3 / kg~0.15m 3 / kg; S13. Cooling gas is introduced to cool the powder obtained in step S12 to room temperature; S14. The powder obtained in S13 is subjected to air classification and sieving to remove agglomerates, and then sealed and packaged under an inert protective atmosphere to obtain modified battery zinc powder.

[0010] The first type of modified battery zinc powder provided in this application is prepared by using a jet hot gas dry processing technology to modify the zinc powder matrix. By controlling the temperature of the mixed hot gas flow, the oxygen volume fraction of the mixed hot gas flow, and the powder feeding speed of the zinc powder matrix, and simultaneously with a cooling and shaping step, zinc oxide particles with uniform dot distribution are generated in situ on the surface of the zinc powder matrix. That is, a continuous oxide film is not formed on the surface of the modified battery zinc powder, and no core-shell coating structure is formed. This can passivate the high activity defects of the zinc powder matrix, and effectively increase the specific surface area through the zinc oxide structure on the surface of the zinc powder matrix. This optimizes the wettability of the electrode electrolyte, uniform zinc ion deposition sites, and suppresses side reactions such as hydrogen evolution or zinc dendrite growth during battery cycle charging and discharging, significantly improving the battery discharge performance, rate performance, and cycle stability.

[0011] Conventional wet processes such as liquid-phase organic passivation and potassium permanganate passivation cover the active sites on the powder surface, reducing the specific surface area and sacrificing battery discharge and rate performance. They also easily introduce impurities. In contrast, the jet hot gas dry processing technology described in this application for modifying the zinc powder matrix requires no addition of any liquid-phase chemical reagents, leaves no impurity residue, exhibits high batch stability, and can be directly adapted to existing industrial production lines for atomized zinc powder. This results in low modification costs and allows for the modification of both irregular zinc powder for mercury-free alkaline manganese batteries and spherical zinc powder for aqueous zinc-based batteries, demonstrating strong versatility.

[0012] Preferably, the feeding speed of the zinc powder matrix is ​​3-7 kg / min.

[0013] Preferably, the temperature of the mixed hot air stream is 340°C to 360°C.

[0014] Preferably, the oxygen volume fraction of the mixed hot gas stream is 2% to 7%, and the volume-to-mass ratio of the mixed hot gas stream to the zinc powder matrix is ​​0.03 m³. 3 / kg~0.07m 3 / kg.

[0015] This application optimizes the volume-to-mass ratio of the mixed hot gas flow to the zinc powder matrix, which facilitates the in-situ generation of zinc oxide particles with a particle size distribution of 200-400 nm and uniform diffusion on the surface of the zinc powder matrix. At the same time, the area ratio of the exposed metallic zinc region on the surface of the zinc powder matrix is ​​controlled at 20%~40%, which can further homogenize the zinc ion deposition sites, thereby guiding the orderly and uniform deposition of zinc ions during the charging and discharging process of the aqueous zinc-based battery, inhibiting dendrite growth, and significantly improving the safety and cycle stability of the aqueous zinc-based battery.

[0016] Preferably, in step S13, the cooling adopts a two-stage gradient cooling mode, wherein the first-stage cooling uses cooling gas at a temperature of 30±5℃, and the second-stage cooling uses cooling gas at a temperature of 10±5℃. This application preferably adopts a two-stage gradient slow cooling mode to prevent abnormal growth of zinc oxide particles and powder agglomeration.

[0017] Thirdly, the second method for preparing modified battery zinc powder provided in this application is as follows: A method for preparing modified battery zinc powder, used to prepare the modified battery zinc powder described in any one of the above-mentioned methods, includes the following steps: S21. Raw material pretreatment: Take battery-grade zinc powder raw material, remove coarse particles and ultrafine floating powder by sieving and air classification to obtain a pure and uniform zinc powder matrix. S22. Place the zinc powder matrix obtained in step S21 into a heat treatment furnace. The thickness of the zinc powder matrix is ​​5mm to 15mm. Heat the matrix to 300℃ to 500℃ at a heating rate of 8℃ / min to 12℃ / min and hold for 0.2h / mm to 1h / mm based on the thickness of the zinc powder matrix. Then, allow it to cool naturally, sieve it, and seal it under an inert protective atmosphere to obtain modified battery zinc powder.

[0018] The second type of modified battery zinc powder provided in this application is also prepared by heat treatment method. The difference is that the heat treatment of the zinc powder matrix in this application is carried out in a heat treatment furnace (such as a muffle furnace). This method can also generate zinc oxide particles in situ with uniform dot distribution on the surface of the zinc powder matrix by strictly controlling the laying thickness of the zinc powder matrix, the treatment temperature and the holding time. However, compared with the above-mentioned dry process of jetting hot gas, the modification efficiency is lower.

[0019] Preferably, the thickness of the zinc powder matrix is ​​5mm to 10mm.

[0020] In summary, this application includes at least the following beneficial technical effects: (1) This application generates zinc oxide particles in situ on the surface of zinc powder matrix in a dotted and uniformly distributed manner, and ensures that the area of ​​exposed metallic zinc region on the surface of zinc powder matrix accounts for 15%~60%, which can improve the specific surface area of ​​modified battery zinc powder and passivate the highly active defect sites on the surface of zinc powder matrix. At the same time, the area of ​​exposed metallic zinc region on the surface of zinc powder matrix is ​​at least 15%, which can meet the basic conductivity and electrochemical activity of zinc powder.

[0021] (2) This application uses a jet hot gas dry processing process to prepare target modified battery zinc powder. By controlling the temperature of the mixed hot gas flow, the oxygen volume fraction of the mixed hot gas flow, and the powder feeding speed of the zinc powder matrix, and with the cooling and shaping steps, zinc oxide particles with a dotted and uniform distribution are generated in situ on the surface of the zinc powder matrix. That is, a continuous oxide film is not formed on the surface of the modified battery zinc powder, and no core-shell coating structure is formed. This can passivate the high activity defects of the zinc powder matrix, and effectively increase the specific surface area through the zinc oxide structure on the surface of the zinc powder matrix. This optimizes the wettability of the electrode electrolyte, the uniform zinc ion deposition sites, and suppresses side reactions such as hydrogen evolution or zinc dendrite growth during battery cycle charging and discharging, significantly improving the battery discharge performance, rate performance and cycle stability.

[0022] (3) This application can also use a heat treatment furnace to prepare modified battery zinc powder. This method can also generate zinc oxide particles in situ on the surface of the zinc powder matrix by strictly controlling the thickness of the zinc powder matrix, the treatment temperature and the holding time.

[0023] (4) Conventional wet processes such as liquid-phase organic passivation and potassium permanganate passivation cover the active sites on the powder surface, sacrificing the battery's discharge performance and rate performance, and are also prone to introducing impurities. However, the zinc powder matrix modified by the jet hot gas dry treatment process or the heat treatment furnace dry heat treatment process described in this application does not require the addition of any liquid-phase chemical reagents, leaves no impurity residue, has high batch stability, and can be adapted to the modification of irregular zinc powder for mercury-free alkaline manganese batteries and spherical zinc powder for aqueous zinc-based batteries, making it highly versatile. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the hot gas atomization powder treatment system used in the hot gas modification of zinc powder in Examples 1-4 of this application.

[0025] Figure 2 This is a scanning electron microscope image of the modified zinc powder in Example 1.

[0026] Figure 3 This is a scanning electron microscope image of the modified zinc powder in Example 2.

[0027] Figure 4 This is a scanning electron microscope image of the modified zinc powder in Example 3.

[0028] Figure 5 This is a scanning electron microscope image of the modified zinc powder in Example 4.

[0029] Figure 6 This is a scanning electron microscope image of the modified zinc powder in Example 5.

[0030] Figure 7 This is a scanning electron microscope image of the modified zinc powder in Example 6.

[0031] Figure 8 This is a scanning electron microscope image of the modified zinc powder in Comparative Example 1.

[0032] Figure 9 This is a scanning electron microscope image of the modified zinc powder in Comparative Example 2.

[0033] Figure 10 This is a scanning electron microscope image of the modified zinc powder in Comparative Example 3.

[0034] Explanation of reference numerals in the attached figures: 1a. Heat treatment chamber; 1b. Powder collection chamber; 2a. Dual-cylinder powder feeder; 3a. Air inlet device; 3b. First filter device; 3c. First air storage device; 3d. Heating device; 3e. Second filter device; 4a. Primary cooling ring; 4b. Secondary cooling ring; 4c. Primary refrigerator; 4d. Secondary refrigerator; 5a. Powder classifier; 5b. Powder collection bin; 6a. Dust collector; 7a. Circulating fan; 7b. Second air storage device; 8a. Third filter device. Detailed Implementation

[0035] The present application will be described in detail below with reference to specific embodiments and comparative examples. In particular, the hot gas modification of zinc powder in the following [Example 1] and [Example 2] is carried out in a hot gas atomization powder processing system.

[0036] Reference Figure 1 The hot gas atomization powder processing system includes a main chamber, a powder feeding unit, a mixed hot gas flow conveying unit, a cooling unit, a powder classification unit, a gas purification unit, and a gas circulation unit.

[0037] Reference Figure 1 The main compartment consists of a heat treatment chamber 1a at the top and a powder collection chamber 1b at the bottom. Heat treatment chamber 1a is where a mixed hot gas flow reacts with the zinc powder matrix. A powder feeding unit and a mixed hot gas flow conveying unit are connected to heat treatment chamber 1a. The powder feeding unit delivers the zinc powder matrix into heat treatment chamber 1a, and the mixed hot gas flow conveying unit delivers the heated mixed hot gas flow into heat treatment chamber 1a. Powder collection chamber 1b is connected to heat treatment chamber 1a. The surface-modified zinc powder matrix enters powder collection chamber 1b and is cooled by a cooling unit.

[0038] Specifically, in this embodiment, a double-cylinder powder feeder 2a is selected as the powder feeding unit. The mixed hot gas flow conveying unit includes an air inlet device 3a, a first filter device 3b, a first gas storage device 3c, a heating device 3d, and a second filter device 3e arranged sequentially along the gas flow conveying direction. The mixed gas stored in the first gas storage device 3c has an oxygen volume fraction of 1% to 15%. The gas in the first gas storage device 3c can be heated to the required temperature by the heating device 3d and filtered by the second filter device 3e before entering the heat treatment chamber 1a. Among them, the air inlet device 3a is used to input gas to adjust the volume fraction of the mixed gas in the first gas storage device 3c, and the first filter device 3b is used to filter and remove impurities from the gas input by the air inlet device 3a.

[0039] Reference Figure 1A cooling unit is installed inside the powder collection chamber 1b to cool the zinc powder matrix after surface modification. The cooling unit includes a primary cooling ring 4a and a secondary cooling ring 4b arranged sequentially from top to bottom. Cooling gas at a temperature of 30±5℃ is introduced into the primary cooling ring 4a, and cooling gas at a temperature of 10±5℃ is introduced into the secondary cooling ring 4b. This gradient and slow cooling of the surface-modified zinc powder matrix prevents powder agglomeration caused by abnormal growth of zinc oxide particles on the surface of the zinc powder matrix. The cooling gas can be air or an inert atmosphere. In this embodiment, for cost considerations, purified recovered gas is used as the cooling gas. To obtain the target cooling gas temperature, the hot gas atomization powder processing system of this embodiment has a primary cooler 4c between the primary cooling ring 4a and the first gas storage device 3c, and a secondary cooler 4d between the secondary cooling ring 4b and the first gas storage device 3c.

[0040] Reference Figure 1 The powder classification unit is connected to the powder collection chamber 1b and is used to screen and classify the zinc powder matrix after surface modification. The powder classification unit can be equipped with one or more powder classifiers 5a to collect target products with different particle size ranges as needed. In this embodiment, the powder classification unit includes two powder classifiers 5a, each with a powder collection bin 5b at its bottom. Specifically, the powder classifier 5a is a cyclone separator.

[0041] Reference Figure 1 The gas purification unit is used to purify the gas output from the main compartment, removing fine powder to obtain reusable purified and recovered gas. The gas purification unit is specifically a dust collector 6a. The gas circulation unit includes a circulating fan and a second gas storage device. The circulating fan recovers the purified and recovered gas obtained from the gas purification unit into the second gas storage device and replenishes it to the first gas storage device 3c.

[0042] In addition, this embodiment also includes an exhaust unit. The hot gas atomization powder processing system can discharge some of the excess purified and recovered gas based on the pressure of the second gas storage device or the oxygen volume fraction in the mixed hot gas flow in the heat treatment chamber 1a. For environmental and safety considerations, the exhaust unit is equipped with a third filter device on the exhaust pipe for filtering the purified and recovered gas. The gas is discharged after further filtration.

[0043] Example

Example 1

[0044] Electron microscopy revealed that the modified battery zinc powder obtained in this embodiment produced in situ a uniformly distributed dot-like zinc oxide particle on its surface. The particle size ranged from 100 nm to 500 nm. ImageJ calculation showed that the area of ​​the exposed metallic zinc region on the zinc powder matrix surface accounted for 58%.

[0045]

Example 2

[0046] Electron microscopy revealed that the modified battery zinc powder obtained in this embodiment produced in situ a uniformly distributed dot-like zinc oxide particle on its surface. The particle size ranged from 200 nm to 400 nm. ImageJ calculation showed that the area of ​​the exposed metallic zinc region on the zinc powder matrix surface accounted for 38%.

[0047]

Example 3

[0048] Electron microscopy revealed that the modified battery zinc powder obtained in this embodiment produced in situ a uniformly distributed dot-like zinc oxide particle on its surface. The particle size ranged from 200 nm to 400 nm. ImageJ calculation showed that the area of ​​the exposed metallic zinc region on the zinc powder matrix surface accounted for 35%.

[0049]

Example 4

[0050] Electron microscopy revealed that the modified battery zinc powder obtained in this embodiment produced in situ a uniformly distributed dot-like zinc oxide particle on its surface. The particle size ranged from 100 nm to 800 nm. ImageJ calculation showed that the area of ​​the exposed metallic zinc region on the zinc powder matrix surface accounted for 18%.

[0051]

Example 5

[0052] Electron microscopy revealed that the modified battery zinc powder obtained in this embodiment produced zinc oxide particles in situ with uniform dot-like distribution on the surface of the modified battery zinc powder. The particle size range of the zinc oxide particles was 50 nm to 200 nm. Using ImageJ, the area ratio of the exposed metallic zinc region on the surface of the zinc powder matrix was calculated to be 60%.

[0053]

Example 6

[0054] Electron microscopy revealed that the modified battery zinc powder obtained in this embodiment produced in situ zinc oxide particles in a uniform, dot-like distribution on its surface. The particle size ranged from 100 nm to 800 nm. ImageJ calculation showed that the area of ​​exposed metallic zinc on the zinc powder matrix surface accounted for 15%.

[0055] Comparative Example Comparative Example 1 The zinc powder matrix that has not undergone modification treatment is the zinc powder matrix obtained in step S11 of Example 1.

[0056] Comparative Example 2 A modified battery zinc powder differs from [Example 1] in that the temperature of the mixed hot gas flow is 700°C and the volume fraction of oxygen is 50%.

[0057] Electron microscopy revealed that the modified battery zinc powder obtained in this comparative example produced an in-situ zinc oxide film on the surface of the modified battery zinc powder, with the area of ​​the exposed metallic zinc region on the zinc powder substrate being approximately 0%.

[0058] Comparative Example 3 A modified battery zinc powder differs from [Example 5] in that: in step S22, the temperature is increased to 700°C at a rate of 8°C / min and held for 2 hours / mm based on the thickness of the zinc powder matrix (i.e., the holding time is 10 hours).

[0059] Electron microscopy revealed that the modified battery zinc powder obtained in this comparative example produced an in-situ zinc oxide film on the surface of the modified battery zinc powder, with the area of ​​the exposed metallic zinc region on the zinc powder substrate being approximately 0%.

[0060] Performance testing Gas evolution test: Add 25g of zinc powder to 135mL of 6mol / L potassium hydroxide solution, seal, and place in an environment of 45℃. Measure the amount of gas evolution of zinc powder over 3 days, calculate the average value, and record the results in Table 1 below.

[0061] Table 1 Results of gas evolution test

[0062] As shown in Table 1, the gas evolution efficiency of the zinc powder in Examples 1-6 is in the range of 6-8 μL / (g·d), and the active sites are moderate. It will not affect the battery discharge efficiency due to slow reaction, nor will it aggravate the occurrence of side reactions due to fast reaction.

[0063] Specific surface area test: The specific surface area of ​​the modified zinc powder obtained in each example and comparative example was tested according to GB / T 19587-2017 "Determination of specific surface area of ​​solid substances by gas adsorption BET method". The results are recorded in Table 2 below.

[0064] Table 2 Specific surface area test results

[0065] Conductivity testing: The conductivity of zinc powder prepared in each example and comparative example was tested according to GB / T 47091-2026 "Determination of Conductivity of Metal Powders". The results are recorded in Table 3 below. The conductivity of the modified battery zinc powder is ≥10. 6 S / m meets the requirements.

[0066] Table 3 Conductivity Test Results

[0067] Based on the above examples 1-6, comparative examples 1-3, and the test results in Table 1-3, it can be seen that: the present application uses a jet hot gas dry processing process or a heat treatment furnace dry processing process. By controlling appropriate process parameters, zinc oxide particles with uniform dot distribution can be grown in situ on the surface of the zinc powder matrix. The particle size of the zinc oxide particles ranges from 50nm to 800nm, and the area of ​​the exposed metallic zinc region on the surface of the zinc powder matrix accounts for 15% to 60%. This can improve the coverage of active points and specific surface area of ​​the battery zinc powder while meeting the basic conductivity requirements of the battery zinc powder, so as to ensure the electrical performance of the battery.

[0068] Battery performance test: Battery sample preparation: Modified zinc powder, used as the negative electrode active material, was mixed uniformly with conductive carbon black and PVDF binder at a mass ratio of 8:1:1. The mixture was then rolled into a film and pressed onto a current collector to prepare the negative electrode sheet. MnO2 was used as the positive electrode, a 2 mol / L ZnSO4 solution as the electrolyte, and a glass fiber membrane as the separator to assemble an aqueous zinc-based battery. The only difference between aqueous zinc-based batteries is the modified zinc powder used as the negative electrode material.

[0069] Coulomb efficiency test: The aqueous zinc-based battery was subjected to 500 charge-discharge cycles at a test current of 0.1C and a test temperature of 25℃. The coulomb efficiency of the aqueous zinc-based battery at the 500th cycle and the 1000th cycle was recorded.

[0070] Table 4. Coulombic efficiency test results of aqueous zinc-based batteries

[0071] Combining the test results in Examples 1-6, Comparative Examples 1-3, and Table 4, it can be seen that compared with unmodified battery zinc powder and modified battery zinc powder whose surface is completely covered by an oxide film, using modified battery zinc powder with a discontinuous oxide layer on the surface as the negative electrode active material is more conducive to suppressing side reactions such as dendrite growth, hydrogen evolution, and corrosion of the zinc negative electrode, so that the aqueous zinc-based battery can maintain a stable high coulombic efficiency after multiple cycles. Among them, the modified battery zinc powder in Examples 2 and 3 has a zinc oxide particle size range of 200-400 nm and an exposed metallic zinc area ratio of 20-40% on the surface of the battery zinc powder, and the aqueous zinc-based battery assembled from these materials has the best coulombic efficiency stability.

[0072] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this specific embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A modified battery zinc powder, characterized in that: The modified battery zinc powder includes a zinc powder matrix and a discontinuous oxide layer grown in situ on the surface of the zinc powder matrix. The discontinuous oxide layer consists of zinc oxide particles that are uniformly distributed in a dotted pattern. The area of ​​the exposed metallic zinc region on the surface of the zinc powder matrix accounts for 15% to 60%, and the particle size of the zinc oxide particles ranges from 50 nm to 800 nm.

2. The modified battery zinc powder according to claim 1, characterized in that: The area of ​​the exposed metallic zinc region on the surface of the zinc powder matrix accounts for 20% to 40%.

3. The modified battery zinc powder according to claim 1, characterized in that: The zinc oxide particles have a particle size range of 100nm to 500nm.

4. A method for preparing modified battery zinc powder, used to prepare the modified battery zinc powder according to any one of claims 1-3, characterized in that, Includes the following steps: S11. Take battery-grade zinc powder raw material, and remove coarse particles and ultrafine floating powder by sieving and air classification to obtain a pure and uniform zinc powder matrix. S12. The zinc powder matrix obtained in step S11 is fed into the heat treatment chamber at a feeding rate of 0.5 kg / min to 10 kg / min. Simultaneously, a mixed hot gas flow with an oxygen volume fraction of 1% to 15% and a temperature of 100℃ to 400℃ is injected into the heat treatment chamber to perform hot gas modification on the zinc powder matrix, so as to grow a discontinuous oxide layer in situ on the zinc powder surface; the volume-to-mass ratio of the mixed hot gas flow to the zinc powder matrix is ​​0.01 m³ / min. 3 / kg~0.15m 3 / kg; S13. Cooling gas is introduced to cool the powder obtained in step S12 to room temperature; S14. The powder obtained in S13 is subjected to air classification and sieving to remove agglomerates, and then sealed and packaged under an inert protective atmosphere to obtain modified battery zinc powder.

5. The method for preparing modified battery zinc powder according to claim 4, characterized in that: The temperature of the mixed hot air flow is 340℃~360℃.

6. The method for preparing modified battery zinc powder according to claim 5, characterized in that: The oxygen volume fraction of the mixed hot gas stream is 2%~7%, and the volume-to-mass ratio of the mixed hot gas stream to the zinc powder matrix is ​​0.03m. 3 / kg~0.07m 3 / kg.

7. The method for preparing modified battery zinc powder according to claim 5, characterized in that: In step S13, a two-stage gradient cooling mode is adopted. The first stage of cooling introduces cooling gas at a temperature of 30±5℃, and the second stage of cooling introduces cooling gas at a temperature of 10±5℃.

8. A method for preparing modified battery zinc powder, used to prepare the modified battery zinc powder according to any one of claims 1-3, characterized in that, Includes the following steps: S21. Raw material pretreatment: Take battery-grade zinc powder raw material, remove coarse particles and ultrafine floating powder by sieving and air classification to obtain a pure and uniform zinc powder matrix. S22. Place the zinc powder matrix obtained in step S21 into a heat treatment furnace. The thickness of the zinc powder matrix is ​​5mm to 15mm. Heat the matrix to 300℃ to 500℃ at a heating rate of 8℃ / min to 12℃ / min and hold for 0.2h / mm to 1h / mm based on the thickness of the zinc powder matrix. Then, allow it to cool naturally, sieve it, and seal it under an inert protective atmosphere to obtain modified battery zinc powder.

9. The method for preparing modified battery zinc powder according to claim 8, characterized in that: The thickness of the zinc powder matrix is ​​5mm to 10mm.